Oxidative stress markers in older pregnant women placentas - Suárez, Silvia Suárez (2007)
Introduction: A factor for obstetrical high risk that contributes to maternal perinatal morbidity and mortality is maternal age over 35. It is possible that the placenta oxidative state of older women is higher than that of younger pregnant women. Objective: To determine placenta oxidative status in pregnant women 35 years or older. Design: Observational, comparative and crosssectional study. Setting: Saint Bartholomew Mother and Child Teaching Hospital and Biochemistry and Nutrition Research Center, Universidad Nacional Mayor de San Marcos. Biological material: Term vaginal childbirth placentas (28) of women 35 years or older and 28 placentas of pregnant women less than 35 year-old. Interventions: Placenta samples were homogenized to 10% with buffer phosphate 10mM, pH 7,4, and centrifuged to 2 000 rpm by 5’. An aliquot of the supernatant was used to analyze lipoperoxidation and glutathione (GSH); the remaining supernatant was centrifuged to 42 000 rpm by 1 hour to determine superoxide dismutase activity (SOD). Main outcome measures: Older and younger mothers’ placenta oxidative status. Results: SOD activity and placental GSH content in older women were respectively 43,52 U/g of tissue and 4,67 x 10-² μmol/mL; values for the control group were respectively 54,13 U/g of tissue and 6,02 x 10-² μmol/mL, both with statistical significant difference (p< 0,05). TBARS (lipoperoxidation) measurements did not show significant differences. Conclusions: Older pregnant placentas showed less antioxidative defence than placentas from younger womens.